Effects of different types of starches on Katjang goat meat emulsion characteristics - Zamzurin, ‘Ainaa’ Nasuha; Ismail, Nur Aqilah; Asyrul-Izhar, Abu Bakar; Kumar, Pavan; Sazili, Awis Qurni; Ismail-Fitry, Mohammad Rashedi (Malaysian Society of Applied Biology, 2024)
Katjang goat meat has the potential to be used for emulsified meat product production but the suitable starch type to be applied as the filler is unknown. The present study was undertaken to evaluate the effect of various starches on the quality characteristic of Katjang goat meat emulsion. Katjang goat meat emulsion was prepared by incorporating various starches viz., tapioca starch (TS), sago starch (SS), and wheat starch (WS), as filler by replacing lean meat. The developed emulsion samples were evaluated for physiochemical, proximate, colour, texture, and gel strength. The addition of TS into meat emulsion results in the most stable emulsion as exhibited by the lowest total expressible fluid (%TEF), expressible fat (%EFAT), and cooking loss. There was no significant (p>0.05) difference for the pH, water holding capacity (WHC), texture profile analysis (TPA), and colour values of all the samples. The incorporation of SS in the formulation decreased (p<0.05) the shear force and work of shearing. In conclusion, the incorporation of TS was found optimum to formulate goat meat emulsion with better quality characteristics.